Upaya Meningkatkan Motorikhalus Melalui Mewarnai Gambar Dengan Menggunakan Coloured Sand Pada Anak Usia 5-6 Tahun Di RA Ar-Ridho TG. Morawa T.A 2021-2022 - Marwiani Widia; Aminda Tri Handayani (Pusdikra Publishing, 2022)
This study aims to find out how to improve children's fine motor skills through coloring pictures using colored sand for children aged 5-6 years at RA Ar-Ridho. This research is a classroom action research (CAR). The subjects of this study were 25 children, consisting of 9 girls and 16 boys. The data collection technique used in this research is the observation of improving children's fine motor skills through coloring pictures with colored sand. teacher and child activities and documentation. The data analysis technique used in this research is descriptive qualitative. Based on the results of the study, it is known that there is an increase in the fine motor skills of children through coloring pictures with colored sand. It is known that on average children who get the level of achievement of children developing as expected (BSH) and developing very well (BSB) in the pre-cycle with an average percentage (12%), then in Cycle 1 the level of achievement of children developing as expected (BSH) and developed very well (BSB) with an average percentage (60%), so we can see an increase in Pre-cycle to Cycle I (48%). However, in the first cycle, it was not well developed so it was continued to the second cycle. The level of achievement of children developing according to expectations (BSH) and developing very well (BSB) Cycle II with an average percentage of 97.5%. Based on the results of the study, it can be concluded that colored sand media can improve children's fine motor skills through 5-6 years.